Wuhan - Sponge City as part of China’s eco-civilization project - Oliveira, Gleiderson Roger Lima de; Rena, Natacha Silva Araújo (ANAP Brazil, 2025)
ABSTRACT Objective – The study aims to understand the decision-making processes that led Wuhan to become an international reference in tackling urban flooding, through the implementation of the Sponge City program, launched by the Chinese government in 2015. It seeks to analyze how these decisions were reflected in the city’s urban design and how they are articulated with China’s eco-civilization project. Methodology – The research was conducted through bibliographic analysis on academic platforms (Google Scholar, Scopus, and other sources) and the investigation of institutional documents from the Chinese government. Urban projects in Wuhan that materialize the most common strategies of the Sponge City program were examined as case studies to evaluate their application and results. Originality/relevance – The study is part of the international debate on urban water management and sustainable urbanism, bringing as a differential the analysis of the Chinese case, which integrates concepts of green-blue infrastructure with local cultural and political traditions. Its academic relevance lies in demonstrating how Wuhan’s model embodies the transition from a logic of impermeabilization to an ecological and resilient approach, serving as an example for urban planning in other parts of the world. Results – Wuhan’s experience showed that the application of the Sponge City concept produced concrete benefits, such as the significant reduction of flooded areas, the expansion of urban permeability, and the creation of multifunctional spaces that combine leisure, aesthetics, and environmental preservation. The history of floods demonstrates that the impacts of inundations were minimized, reinforcing the feasibility of this strategy in the contemporary urban context. Theoretical/methodological contributions – The study provides a technical and methodological framework on the strategies applied in the Sponge City program, such as rain gardens, permeable pavements, green roofs, and retention basins. It also highlights the importance of integrating master plans, national regulations, and local guidelines as tools for replication in different urban contexts. Social and environmental contributions – The study shows that the Sponge City promotes social and environmental gains by improving the relationship between people and the urban environment, reducing disaster risks, expanding green areas, and encouraging citizen participation in planning processes. Wuhan’s experience contributes to sustainable public policies, strengthens the perspective of eco-civilization, and reaffirms the role of water as a structuring element of urban quality of life.